Linking paternally inherited mtDNA variants and sperm performance - Bettinazzi, Stefano; Nadarajah, Sugahendni; Dalpé, Andréanne; Milani, Liliana; Blier, Pierre U.; Breton, Sophie (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2020)
Providing robust links between mitochondrial genotype and phenotype is of major importance given that mitochondrial DNA (mtDNA) variants can affect reproductive success. Because of the strict maternal inheritance (SMI) of mitochondria in animals, haplotypes that negatively affect male fertility can become fixed in populations. This phenomenon is known as ‘mother's curse’. Doubly uniparental inheritance (DUI) of mitochondria is a stable exception in bivalves, which entails two mtDNA lineages that evolve independently and are transmitted separately through oocytes and sperm. This makes the DUI mitochondrial lineages subject to different sex-specific selective sieves during mtDNA evolution, thus DUI is a unique model to evaluate how direct selection on sperm mitochondria could contribute to male reproductive fitness. In this study, we tested the impact of mtDNA variants on sperm performance and bioenergetics in DUI and SMI species. Analyses also involved measures of sperm performance following inhibition of main energy pathways and sperm response to oocyte presence. Compared to SMI, DUI sperm exhibited (i) low speed and linearity, (ii) a strict OXPHOS-dependent strategy of energy production, and (iii) a partial metabolic shift towards fermentation following egg detection. Discussion embraces the adaptive value of mtDNA variation and suggests a link between male-energetic adaptation, fertilization success and paternal mitochondria preservation. This article is part of the theme issue ‘Linking the mitochondrial genotype to phenotype: a complex endeavour’.